Arithmetic and manipulable objects: a methodological proposal for the early years of elementary school (Research, Society and Development, 2020)
Considering the results obtained in large-scale assessments, carried out both at national and international level, Prova Brasil and PISA respectively, which point out worrying data regarding the development of skills relevant to mathematics, we are concerned with investigating the possible causes for school failure. In this sense, we shed light on the pedagogical practices developed in the early years of elementary school, in view of the little diversity of pedagogical resources used in the classroom, since the book and notebook predominate. We aim to reflect on the use of manipulable materials, especially gold material, in the process of teaching and learning the properties of the decimal numbering system and, consequently, of mathematical calculation in the early years of elementary school. To this end, we use the bibliographic research aiming to expand our conceptions and enable a better discussion about the phenomenon in question. After the readings and reflections, there was a consensus among the authors regarding the importance and benefits of using manipulable materials in mathematics classes.